Pemetaan Model Pembelajaran Bola Voli untuk Peningkatan Motivasi Siswa: Analisis Bibliometrik Terhadap Tren Penelitian Global - Julkifli Buyunggadang; Hariadi Said; Rosbin Pakaya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
Physical education learning models, especially those related to volleyball, increasingly emphasize the importance of improving student motivation as the basis for student success and engagement. A systematic bibliometric analysis method was used in this study to identify trends, intellectual structures, and global development directions in research on volleyball learning models to increase student motivation. Data were obtained from the Scopus database for the period 2015\--2024 using a keyword-based search strategy, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Of the 1,199 initial documents, 600 English-language journal articles met the inclusion criteria, and VOSviewer software was used to perform the analysis. The United States contributed the most with 150 articles, followed by Indonesia 55 articles and China 45. The interdisciplinary nature of this research is evident from the bibliometric analysis. It covered the fields of medicine, health professions, social sciences, and psychology. Keyword network visualization distinguished two main categories: (1) pedagogical aspects (learning models, learning strategies, skill development) and (2) psychological dimensions (motivation, anxiety, athletic performance), with motivation serving as the main connector. Keywords: Bibliometric Analysis, Volleyball, Learning Model, Learning Motivation, PRISMA, VOSviewer